2017
DOI: 10.1155/2017/6593913
|View full text |Cite
|
Sign up to set email alerts
|

Diagenesis and Fluid Flow Variability of Structural Heterogeneity Units in Tight Sandstone Carrier Beds of Dibei, Eastern Kuqa Depression

Abstract: Tight sand gas plays an important role in the supply of natural gas production. It has significance for predicting sweet spots to recognize the characteristics and forming of heterogeneity in tight sandstone carrier beds. Heterogeneity responsible for spatial structure, such as the combination and distribution of relatively homogeneous rock layers, is basically established by deposition and eodiagenesis that collectively affect the mesogenesis. We have investigated the structural heterogeneity units by petrofa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Based on the homogenization temperature distribution of aqueous fluid inclusions (converted to age via the thermal history), petroleum charge can be divided into two stages: 25 Ma to 12 Ma and 5 Ma to the present day (Figure 14). These results are consistent with the results of Li et al [30,31] and Shi et al [32]. They indicated that since the deposition of the Miocene Jidike Formation (23 Ma-), the Triassic source rocks began to enter the mature stage; when the Pliocene Kuqa Formation deposited (5 Ma-), the Triassic source rocks reached the peak of gas generation and migration, and the Jurassic source rocks entered the mature stage to generate oil and gas.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Based on the homogenization temperature distribution of aqueous fluid inclusions (converted to age via the thermal history), petroleum charge can be divided into two stages: 25 Ma to 12 Ma and 5 Ma to the present day (Figure 14). These results are consistent with the results of Li et al [30,31] and Shi et al [32]. They indicated that since the deposition of the Miocene Jidike Formation (23 Ma-), the Triassic source rocks began to enter the mature stage; when the Pliocene Kuqa Formation deposited (5 Ma-), the Triassic source rocks reached the peak of gas generation and migration, and the Jurassic source rocks entered the mature stage to generate oil and gas.…”
Section: Discussionsupporting
confidence: 94%
“…Jidike Formation, the Ahe Formation underwent rapid subsidence and burial and entered the mesodiagenetic stage (Figure 14). In the late Oligocene, the Triassic source rocks entered the threshold of hydrocarbon generation [31,32]. The thermal degradation of organic matter released a large amount of organic acids and CO 2 followed or accompanied by oil generation [38][39][40].…”
Section: Mesodiagenesis Since the Deposition Of The Miocenementioning
confidence: 99%